Diversity of Parasitoids Hymenoptera in Agricultural Ecosystems and Primary Forest in Lubuk Kilangan District, Padang - Hasmiandy Hamid; Alfala Hakiki; Munzir Busniah; Zahlul Ikhsan; Stefan Schmidt (Universitas Andalas, 2023)
Parasitoid Hymenoptera is an important natural enemy of most plant pests, and it can control pests specifically in the agricultural ecosystem. The study aimed to study parasitoid Hymenoptera diversity in agricultural and primary forest ecosystems. The research was conducted from March to June 2018 at Lubuk Kilangan Subdistrict, Padang. The research location was determined by purposive sampling, and sampling was taken using malaise and yellow traps. The results showed that the family of parasitoid Hymenoptera with dominant numbers of individuals and morphospecies were Braconidae, Ichneumonidae, and Scelionidae. The diversity index of both ecosystems is classified as high, with a value of 4,879 for primary forest ecosystems and 4,675 for agricultural ecosystems. The Evenness index of both ecosystems is classified in the high category, with a value of 0,905 for the primary forest ecosystem and 0,887 for the agricultural ecosystem. The similarity index of both ecosystems is classified in the high category with a value of 0,607.